2013
DOI: 10.1063/1.4801809
|View full text |Cite
|
Sign up to set email alerts
|

Crossover from weak localization to anti-weak localization in indium oxide systems with wide range of resistivity

Abstract: We investigated the magnetoconductivity Δσ(H)≡1/ρ(H)−1/ρ(0) in a wide range of magnetic fields for three-dimensional indium oxide films doped with zinc, tin, or gallium in the range of resistivity ρ(300K) between 4.1×10−6 Ωm and 1.7×10−3 Ωm. The weak localization theory was fitted to data for Δσ(H) at various temperatures in the range 2.0 K≤T≤50 K by the use of suitable characteristics Dτin(T) and Dτso, where D, τin, and τso are the electron diffusion constant, inelastic scattering time, and spin-orbit (s-o) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Because of this weak localization of electrons, the resistivity r varies as r f ÀT ½ in disordered three-dimensional (3-D) systems and as r f Àln T in twodimensional (2-D) systems [7]. These theoretical predictions of WL have experimentally been confirmed in many semiconducting as well as metallic thin films [8,9].…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Because of this weak localization of electrons, the resistivity r varies as r f ÀT ½ in disordered three-dimensional (3-D) systems and as r f Àln T in twodimensional (2-D) systems [7]. These theoretical predictions of WL have experimentally been confirmed in many semiconducting as well as metallic thin films [8,9].…”
Section: Introductionmentioning
confidence: 72%
“…7. It may be noted that all the three samples show a negative MR, and its magnitude increases with decrease in temperature at a field of about 0.9 T. A maximum MR of 1.5% is obtained for a 10 nm thick film at 18 K. The MR in a nonmagnetic semiconductor can be attributed to several effects, including WL effects [7,9,15] weak anti-localization effects [9], electroneelectron interactions [7,15], and superconducting fluctuation effects [20,21]. The weak anti-localization effects and superconducting fluctuation effects are known to always result in positive MR, while the WL effect results in negative MR. Electroneelectron interaction (EEI) manifests itself in the presence of higher magnetic fields than the WL does [7], and in the present case, the MR is observed in the relatively low magnetic field (B 1 T).…”
Section: Magneto Transport Behaviormentioning
confidence: 91%
“…3 is also an important aspect in quantum interference study. A transition from a WAL to a WL state was found in three-dimensional a-IGZO films as T is increased [23], while WAL in our device survives at higher T with the WL behavior at B 0.035 T evolves into a plateau. According to the HLN theory for 2D systems [14], the system favors WL when the energy relaxation time decreases at higher T and becomes shorter than the spin-orbit interaction time or the magnetic scattering time.…”
mentioning
confidence: 81%
“…Quantum interference and weak localization have been explored in three-dimensional and low-dimensional electron systems in various materials [14][15][16][17][18][19][20][21]. Indium zinc oxide (IZO) films and nanowires [22][23][24][25][26][27] in particular have raised special interest because of their potential applications in modern technologies. However, a comprehensive, in-depth study of lowtemperature electrical transport in IZO is still missing, and the underlying mesoscopic and microscopic mechanisms remain largely unclear.…”
mentioning
confidence: 99%
“…The capability of tuning the spin-orbit coupling strength might be useful for the future implementation of nanoscale spintronic devices [160]. Recently, Shinozaki et al [161] have observed an increasing ratio (1/τ so )/(1/τ N ee,3D ) with increasing ρ in a series of amorphous indium-zinc-oxide and indium-(tin,gallium)-zinc-oxide thick films.…”
mentioning
confidence: 99%